Detection of interference in slow FH/16-QAM systems using generalized likelihood ratio test - Aung, Aye (2013)
In this paper, we propose a generalized likelihood ratio test (GLRT)-based algorithm to detect the interference encountered in slow frequency-hopped 16-ary quadrature amplitude modulation (FH/16-QAM) systems. Both multitone interference (MTI) and partial-band noise interference (PBNI) are considered. By using the GLRT for the linear model, we derive the close-form expression for the test statistic which is expressed in terms of the received signal and interference signal. The corresponding detection threshold is also derived based on a fixed probability of false alarm, which can be known as a constant false alarm rate detector. The results show that the proposed GLRT method is able to provide good detection performance for both types of interference even at low interference power, that is, 6 dB lower than signal power. Moreover, it is shown that the algorithm can also be used to detect the interference under unknown interference dominant environment without having the knowledge of type of interference for detection.